Affective Commitment: The Mediating Role of Job Satisfaction (A Study on Five Star Hotel in Surabaya): Komitmen Afektif: Peran Mediasi Kepuasan Kerja (Studi pada Hotel Bintang Lima di Surabaya) - B. Medina Nilasari; Nikita Suwandi (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2025)
This study aims to analyze the influence of human resources management practices (HRM practices) and organizational communication on affective commitment mediated by job satisfaction. The sample was employees of Five Star Hotels in Surabaya. With the purposive sampling method, 180 respondents were obtained as samples. The results showed that recruitment & selection and organizational communication had an effect on job satisfaction, while training & socialization and employment security had no effect on job satisfaction. Training & socialization, employment security, and job satisfaction have an effect on affective commitment, while recruitment and selection have no effect on affective commitment. Job satisfaction as a mediating variable can strengthen the influence of HRM practices on affective commitment and the influence of organizational communication on affective commitment.